Larva migrans within scalp sebaceous gland - Guimarães,Lucinda Calheiros (1999)
A case of larva migrans or serpiginous linear dermatitis on the scalp of a teenager is reported. An ancylostomid larva was found within a sebaceous gland acinus. The unusual skin site for larva migrans as well as the penetration through the sebaceous gland are highlighted. The probable mechanism by which the parasite reached the skin adnexa is discussed.